Treatment choice for early-stage hepatocellular carcinoma in real-world practice: impact of treatment stage migration to transarterial chemoembolization and treatment response on survival. (2nd November 2018) - Roberts, Stuart K.; Gazzola, Alessia; Lubel, John; Gow, Paul; Bell, Sally; Nicoll, Amanda; Dev, Anouk; Fink, Michael A.; Sood, Siddharth; Knight, Virginia; Hong, Thai; Paul, Eldho; et al.
Abstract: Objective: The objectives of our study were firstly to characterize the treatment stage migration phenomenon in early (Barcelona Clinic Liver Cancer [BCLC]-0/A) stage hepatocellular carcinoma (HCC) by comparing the efficacy of curative therapies with trans-arterial chemoembolization [TACE] and secondly, determining baseline and on-treatment predictors of survival. Methods: All patients within BCLC-0/A stage from six tertiary hospitals who received curative therapy with either resection, transplantation, or ablation or TACE as first-line treatment were included in the analyses. The primary endpoint was overall survival; secondary end-points were transplant-free survival and recurrence-free survival. Results: Between January 2000 and December 2013, we identified 253 BCLC-0/A HCC patients of whom 148 (58.5%) received curative therapy and 105 (41.5%) migrated to TACE. Patients undergoing TACE had lower median survival (2.7 vs. 6.7 years; p  < .0001), transplant-free survival (2.6 vs. 4.8 years; p  < .0001) and recurrence-free survival (1.3 vs . 2.7 years; p  < .001). On multivariate analysis treatment allocation to TACE was an independent prognostic predictor for both lower overall survival (HR 1.70, p  = .04) and for HCC recurrence (HR 2.25, p  < .001). The main prognostic determinant for each target outcome was Child-Pugh score. Conclusions: Our study confirms that curative treatments should always be preferred when applicable in early-stage HCC, but that in cases where this is not possible, TACE is a reasonable albeit inferior treatment option. In addition, it provides unique prognostic information on a significant proportion of patients with early-stage disease in whom curative therapy is not applicable.